2018
DOI: 10.1177/1063426618769067
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Treatment Integrity and Acceptability of Check & Connect

Abstract: The study reports the treatment integrity and acceptability of Check & Connect (C&C), after implementation by 234 adult mentors with 341 students with social, emotional, and behavioral problems. To address the gaps in the treatment acceptability literature, the study further explored (a) the relation between treatment integrity and treatment acceptability of C&C and (b) the predicted effects of variables investigated in the analog studies on mentors’ treatment acceptability ratings. Overall, mentor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To date, only one study specifically examined whether the variables identified in the literature to influence treatment acceptability would hold true in C&C (Tsai & Kern, 2018). The results showed that the critical variables such as student behavior severity, students’ special education classification, and adults’ work experience did not predict C&C mentors’ acceptability ratings.…”
mentioning
confidence: 99%
“…To date, only one study specifically examined whether the variables identified in the literature to influence treatment acceptability would hold true in C&C (Tsai & Kern, 2018). The results showed that the critical variables such as student behavior severity, students’ special education classification, and adults’ work experience did not predict C&C mentors’ acceptability ratings.…”
mentioning
confidence: 99%